2017
DOI: 10.1155/2017/4218472
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspects of Bone Health and Fracture Healing

Abstract: Introduction Fractures are quite common, especially among the elderly. However, they can increase in prevalence in younger ages too if the bone health is not good. This may happen as a result of bad nutrition. Methods A customized, retrospective review of available literature was performed using the following keywords: bone health, nutrition, and fractures. Results Insufficient intake of certain vitamins, particularly A and D, and other nutrients, such as calcium, may affect bone health or even the time and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 64 publications
1
46
0
2
Order By: Relevance
“…An appropriate dietary intake of calcium (Ca), as the principal component of bone, can significantly reduce bone loss and it is crucial to replenish daily Ca losses. When the Ca intake is insufficient, the organism is forced to increase the process of osteolysis to maintain homeostasis [26]. The obtained results confirmed that Ca dietary restriction (60% recommended dose) caused a significant decrease in ionized calcium, phosphorus concentration in serum, as well as the activity of alkaline phosphatase (bone turnover parameter).…”
Section: Discussionsupporting
confidence: 63%
“…An appropriate dietary intake of calcium (Ca), as the principal component of bone, can significantly reduce bone loss and it is crucial to replenish daily Ca losses. When the Ca intake is insufficient, the organism is forced to increase the process of osteolysis to maintain homeostasis [26]. The obtained results confirmed that Ca dietary restriction (60% recommended dose) caused a significant decrease in ionized calcium, phosphorus concentration in serum, as well as the activity of alkaline phosphatase (bone turnover parameter).…”
Section: Discussionsupporting
confidence: 63%
“…We chose potential confounder candidates for evaluation according to the suggestions of the literature: gestational age, education years, adult height, lifelong physical activity, lifelong smoking history, and adulthood diet . Gestational age (in weeks) was recorded at the maternity hospital.…”
Section: Methodsmentioning
confidence: 99%
“…In young healthy patients, bone tissue shows high self-repair abilities. However, systematic factors, such as an increased age, disease or obesity can negatively affect bone regeneration [ 1 , 2 , 3 ]. Large defects due to heavy trauma, multiple fracture, infection, or tumor resection, are also disruptive for proper tissue healing [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%